PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENURUNAN TINGKAT KENAKALAN REMAJA SANTRI KELAS X SMA BABUSSALAM PEKANBARU TAHUN AJARAN 2013/2014 - Mutia Sahira Sahira; Abu Asyari Asyari; Raja Arlizon Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: "The Effect of Guidance Group Service Against Delinquency Rate Decrease Class X SMA Babussalam Pekanbaru in Academic Year 2013/2014". The purpose of this research are: (1) To determine the level of  juvenile delinquency picture students in class X SMA Babussalam Pekanbaru before the implementation of the guidance group (2) To determine the level of juvenile delinquency picture students in class X SMA Babussalam Pekanbaru after the implementation of the guidance group (3) To know the different levels of juvenile delinquency students of class X SMA Babussalam Pekanbaru before to after the implementation of the guidance group (4) To determine the effect of the decrease in the level of group counseling juvenile delinquency students in class X SMA Babussalam Pekanbaru. The population was 102 students or all students of class X, the sample size in this study was 15% of the population is 16 students. This research method is quasi experiment. The results based on calculations thitung greater than ttable at a rate of 5% (5.86> 2.042). Then, there are significant differences between juvenile delinquency level before the after-class implementation guidance services group X Babussalam Pekanbaru. Keywords: Guidance group, Juvenile Delinquency